Scoring performance of European professional basketball players: a comparison between domestic leagues and the Eurobasket - Gómez, M. A.; Vaquera, A.; Filho, E.; Zong, S. (International Journal of Performance Analysis in Sport, 2025)
This study classified European basketball players participating in EuroBasket 2022 based on physical attributes, playing time, experience, and scoring statistics, while analysing scoring performance differences across NBA, Euroleague, and EuroBasket competitions. A sample of 82 European players with a minimum of 5 minutes per game in the NBA (n = 27) or Euroleague (n = 55) was categorised into four profiles: Important Guards (IG), Important Forwards (IF), Big Men Less Important (BMLI), and Big Men Important (BMI). The NBA featured more IG and BMLI players, while the Euroleague had a higher proportion of IF. Scoring performances varied significantly across competitions. Euroleague BMLI players excelled in EuroBasket, particularly in points and free throws, while IF players improved in successful 3-point field goals. BMI players struggled with lower success in 2-point field goals. NBA BMLI and BMI players exhibited fluctuations in 2-point field goals, while IG players adjusted their points scored and 3-point success rates during EuroBasket. These results highlight league-specific demands shaping player performance, providing coaches and managers with insights to optimise player utilisation and tactical planning for transitions between domestic and international competitions, enhancing team effectiveness.